Irish University Press series of British parliamentary papers : minutes of evidence before the select committees on the affairs of the East India company with appendices and indices [V military ] [VI political of foreign 1831-32 : Vol 11 : colonies East India - Great Britain. Parliament. House of Commons (Shannon : Irish University Press, 1970)
This set consolidates all papers relating to penal colonies covering the period 1810-1869. Australian content is prevalent through all 16 volumes.
Title on spine: British parliamentary papers.
v. 1 published 1969.
Each vol. has a distinctive individual subtitle.
From the collection of Angus Downie, a well respected political journalist for The Examiner in Launceston, Tasmania and noted disability campaigner.
Keywords: Penal colonies -- Great Britain -- History -- Sources